Optimization of Traffic Education and Public Awareness in Traffic Order - Aditya Ramadhan Hidayat (Advances in Police Science Research Journal, 2024)
The number of traffic accidents in the Tasikmalaya district police jurisdiction increases every year. This results in the failure to achieve public order and safety, especially road users. Therefore, traffic accidents are a prominent problem in the Tasikmalaya district police jurisdiction. Therefore, efforts from the education and engineering unit are needed to prevent traffic accidents, one of which is public education about Traffic in the Strict Order Traffic Village. In research conducted as a knife analysis in discussing problems in research using Management Theory, Communication Theory, the concept of public education about traffic, the concept of optimization, the concept of an orderly village, and the concept of traffic accidents. This research uses a qualitative approach and also the type of research in the form of field research. The focus of the research lies in the implementation of an orderly village conducted by the education and engineering unit with Tasikmalaya police personnel and the community as a source of data. In the method of data collection this writing conducts interviews, observations, and studies of documents. Furthermore, the validity of the data is proven by data triangulation. While data analysis techniques include data reduction, data presentation, and drawing conclusions. The results of this research are (1) Lack of community participation both in the traffic order village and surrounding areas to carry out community education programs on traffic in the midst of traffic accidents, (2) Less optimal implementation of community education about traffic in the village orderly traffic cross as a medium to increase public awareness of ethics for orderly traffic, (3) Lack of ability of education and engineering unit personnel in the management of implementation as well as communication skills of personnel and number of personnel Based on the research findings, it is suggested to the head of the traffic unit to add personnel in the education and engineering unit as well as to collaborate with relevant agencies to support the implementation of the traffic order village, and to the head of the unit and members of the education and engineering unit to improve communication skills with the community and conduct more innovative and creative activities so that the ethical awareness of traffic increases to prevent traffic accidents.